EU SOU A LUZ DO MUNDO: UM ESTUDO DO SIGNIFICADO DO TERMO LUZ EM JOÃO 9, 1-41 - Almeida, Maria Aparecida de Andrade (2008)
The word light inserts itself in the encounter of the old Testament and Greco-Roman traditions as an alternative to certain needs of the Johannine community: the different cultures of the people who received the Gospel; the diversity of problems that were asking for different answers; the class differences inside the community; the contradictory positions taken against imperial politics and the conflict between Jews and Christians. And it is in this conflicting interim, both internal and external, a painful moment for the dissidents (because the damage was not just religious, but they caused changes in all aspects of life) that Johannine community shall seek some alternative. Therefore the Narrative of the Blind Man s Healing (Jo 9,1-41) works as a mirror for that community who will look to Jesus for the light that it needs to keep going on. The blind man represents the community before knowing the Light of the World. Solidarity, fraternity and mutual love are powers that did help in the resistance.(AU)